UPAYA MENINGKATKAN KETERAMPILAN MENULIS PARAGRAF NARASI MENGGUNAKAN MODEL PEMBELAJARANCONTEXTUAL TEACHING LEARNING (CTL)PADA SISWA KELAS III SEKOLAH DASAR - Umi Arlini Ramayanti; Maria Friska Nainggolan (Jurnal Mutiara Pendidikan Indonesia, 2018)
This study aims to improve the skills of narrative writing through Contextual Teaching and Learning (CTL) learning class III SD Swasta Bakti Luhur. The type of this research is Classroom Action Research (PTK). This research is conducted two cycles that each cycle consists of planning, action, observation, and reflection. The subjects of the study were the fourth grade students of SD Swasta Bakti Luhur, which amounted to 33 students. Data collection techniques used observation, documentation, and test. The results showed that the skills of students in writing paragraph narrative have increased. Percentage of students writing skill score of first cycle was 36,36%. And Percentage of student writing skill score of second cycle was 90,90 %.